The dose-response relationship between dairy product intake and all-cause and cardiovascular mortality risk: a systematic review and meta-analysis of prospective cohort studies - Hu, Xiaomeng; Wang, Kaiyang; Ji, Xing; Wang, Xinwei; Bai, Peiyan; Huang, Kailin; Lu, Aimei; Li, Jingen; Wu, Huanlin (Frontiers in Nutrition, 2026)
Background and aimsThe dose–response relationship between dairy product intake and mortality from all-causes and cardiovascular mortality remains controversial. While dairy products are key sources of essential nutrients, their health effects appear highly heterogeneous, varying by product type, fat content, and processing methods. For example, some studies suggest whole milk increases mortality risk compared to low-fat milk, while other expert reviews from the same year conclude that dairy’s link to CVD risk is neutral regardless of fat content. This systematic review and meta-analysis aimed to clarify this association by examining different dairy categories.MethodsWe systematically searched PubMed, Web of Science, and Embase up to June 19, 2025, for prospective cohort studies in healthy adults that reported risk estimates for the association between dairy intake and all-cause or cardiovascular mortality. Linear and restricted cubic spline models were used for dose–response analysis. From 4,797 retrieved articles, 29 prospective cohort studies involving 1,680,651 participants were included.Results and conclusionsOur findings indicate that yogurt consumption (200 g/day) was associated with a reduced risk of both all-cause (HR: 0.89; 95% CI: 0.83, 0.96) and cardiovascular mortality (HR: 0.89; 95% CI: 0.83, 0.95). Cheese intake (15 g/day) was linked to a lower risk of CVD mortality only (HR: 0.95; 95% CI: 0.91, 0.99). Milk consumption (200 g/day) was associated with reduced CVD mortality in the non-sex-stratified group (the 7 studies) (HR: 0.86; 95% CI: 0.75, 0.98). Total dairy intake showed a U-shaped association with both mortality outcomes, with an optimal intake of approximately 250–300 g/day. These results highlight that the health effects of dairy are dependent on the specific product type and dose. Fermented dairy products, particularly yogurt, appear to be more beneficial. Our findings do not support the generalized conclusion that all dairy products uniformly protect against mortality, emphasizing the need for more nuanced dietary recommendations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251067824 Identifier: CRD420251067824.